Why do Firms Operate Informally? Insights from a Systematic Literature Review - Florencia Verónica Pedroni (Universidad Nacional de Colombia, 2021)
This paper investigates factors that motivate entrepreneurs to completely operate within informality and the drivers of formal companies to underreport revenues. In particular, this work identifies and organizes the determinants of firm informality through a systematic literature review in Scopus and Web of Science databases. The article presents several contributions. First, it examines the two main frameworks of informality (structuralist/exclusion and legalistic/exit dimensions) and links this with the different roles of unregistered firms in economic development (survival, De Soto, and parasite views). It also studies the theoretical basis of informality, including economic, institutional, psychological, and sociological aspects. Second, the paper summarizes business informality determinants based on studies with different methodological approaches (macro, microeconomic), contexts (developed, emerging, transition economies), and periods (1983-2018). Our results show that firm informality is mostly addressed in the examined literature as a decision or voluntary choice by companies and entrepreneurs (legalistic vision). Third, the article proposes an integral theoretical model, according to which the firm informality level is determined by structural elements (company and entrepreneur’s characteristics) and environmental factors (corruption, bureaucracy, taxes, etc.). The analysis is relevant for researchers studying this subject and for policymakers as well.